Full-biodegradable foamed plastic and preparation method thereof

By optimizing the PLA formula and supercritical CO2 foaming process, the problems of large cell diameter and high density of existing biodegradable PLA foam materials have been solved, and the preparation of all biodegradable foam plastics with high cell density and excellent mechanical properties have been achieved. Significantly improves foaming ratio and compression performance.

CN119242007APending Publication Date: 2025-01-03CHANGZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411526191.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing biodegradable PLA foam materials have large cell diameters and high density, which affects its mechanical properties and degradation properties.

Method used

The optimized PLA formulation and supercritical CO2 foaming process include the use of double epoxy functional chain extenders, allyl diethylene glycol dicarbonate as chain extenders, and polytetrafluoroethylene particles as nucleating agents, and through The cooling process destroys the crystal region structure and forms a PLA foaming material with high foaming ratio and high bubble cell density.

Benefits of technology

A fully biodegradable foam plastic with large cell density, small diameter and excellent mechanical properties was prepared, which significantly improved the foaming ratio and compression performance, while retaining the biodegradable properties of PLA.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005109279850000061
    Figure BDA0005109279850000061
  • Figure BDA0005109279850000081
    Figure BDA0005109279850000081
  • Figure BDA0005109279850000082
    Figure BDA0005109279850000082
Patent Text Reader

Abstract

The invention discloses full-biodegradable foamed plastic and a preparation method thereof, and belongs to the technical field of foaming materials, and the full-biodegradable foamed plastic is prepared from the following raw materials in parts by mass: 100 parts of polylactic acid, 0.1-0.5 part of an initiator, 0.5-3 parts of a chain extender, 0.1-0.3 part of an antioxidant, 0.5-2 parts of a plasticizer, 8-10 parts of an additive and 1-4 parts of a nucleating agent. The preparation method comprises the following steps: preparing long-chain branch PLA with low gel content through an initiator and a chain extender, then increasing nucleation sites by adopting a micron-sized nucleating agent, and preparing the fully biodegradable PLA foamed plastic through a supercritical fluid foaming process of heating and cooling. The full-biodegradable foamed plastic disclosed by the invention is good in foam pore morphology, small in foam pore size and uniform in foam pore distribution, and the foam pore density is remarkably improved; the gel is low in content, degradable and environment-friendly; the compression performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of foaming materials, and in particular to a fully biodegradable foam and a preparation method thereof. Background Art

[0002] Polymer materials are widely used due to their advantages such as light weight, durability and excellent performance. However, their sources consume a large amount of petroleum resources. In addition, due to the long degradation cycle or incomplete degradation, a large amount of carbon dioxide will be released during incineration, causing "white pollution" and "greenhouse effect". In order to achieve a sustainable low-carbon circular society, the development of biodegradable polymer materials to replace ordinary petroleum-based polymer materials has become a hot topic of concern. At present, commercialized bio-based degradable polymer materials include thermoplastic starch, polylactic acid, polycaprolactone, etc. These materials account for 80%-90% of the market share of biodegradable materials. Among the existing biodegradable polymer materials that have been developed and utilized, polylactic acid (PLA) has been widely studied and applied, and is known as the most promising biodegradable polymer. PLA is completely biodegradable and plant-derived with renewable resources as raw materials, and is a material that maintains the "carbon cycle balance" in nature.

[0003] Foam is a special material with a porous structure. The composite structure of solid phase encapsulating gas phase and the huge difference in properties between solid phase and gas phase make foam a unique combination with special properties to meet different application requirements. The expansion ratio of up to several dozen times also reduces the weight of foam materials to a few or even tens of times of the raw materials, which makes foam materials more and more valued in terms of environmental protection and energy saving. Supercritical CO2-based foaming technology has become a hot research direction in the industry and academia due to its advantages in micro-nanopore molding, environmental protection and price.

[0004] Patent CN201910551355.2 discloses a method for preparing a biodegradable PLA microporous foam material, in which triepoxypropyl isocyanurate is used as a chain extender and nano-organic montmorillonite is used as a nucleating agent, and a degradable PLA foam material is successfully prepared by extrusion foaming, but the average pore diameter of the foam is 45μm-86μm, which is much higher than the 16μm-28μm of the present invention. Patent CN202010265302.7 discloses a PLA / PA supercritical foaming composite material and a preparation method thereof, which uses 4-hydroxyethyloxyethyl-1-hydroxyethyl benzene diether as a chain extender to improve the foaming performance of the material, and uses a mixture of tert-butyl hydroperoxide and diisopropylbenzene peroxide as an organic peroxide, which have a good synergistic effect and improve the resilience and comprehensive mechanical properties of the foaming material. However, the mixture of tert-butyl hydroperoxide and dicumyl peroxide makes polylactic acid, polyamide, polysiloxane-polyimide block copolymer composite crosslinking (vulcanization), which reduces the degradation performance of the foaming material. The average diameter of the prepared foam pores is 57μm-95μm, and the density is 0.60g / cm 3 -0.72g / cm 3 , the density is one order of magnitude higher than that of the present invention. Summary of the invention

[0005] The invention provides a fully biodegradable foam and a preparation method thereof, the main purpose of which is to prepare a fully biodegradable foam plastic with high cell density, small diameter and excellent mechanical properties.

[0006] In order to achieve the above-mentioned purpose of the present invention, the present invention provides a fully biodegradable foam plastic, which is made from the following raw materials in mass fractions: 100 parts of polylactic acid (PLA), 0.1-0.5 parts of initiator, 0.5-3 parts of chain extender, 0.1-0.3 parts of antioxidant, 0.5-2 parts of plasticizer, 8-10 parts of additives, and 1-4 parts of nucleating agent.

[0007] Furthermore, the PLA is L-polylactic acid with an optical purity greater than 85% and a density of 1.24 g / cm 3 Preferably, the optical purity of the poly(L-lactic acid) is greater than 96%, such as LX175; or L-polylactic acid with an optical purity of >98%, 99%, such as LX575, L175, etc.

[0008] Furthermore, the chain extender includes at least one of a diepoxy functionalized chain extender, a bisallyl chain extender, and a bisacrylate chain extender.

[0009] Preferably, the diepoxy functionalized chain extender includes but is not limited to at least one of diglycidyl ether and neopentyl glycol diglycidyl ether.

[0010] Preferably, the bisallyl chain extender includes but is not limited to at least one of allyl diethylene glycol dicarbonate (DOEDB) and bisphenol A bisallyl ether;

[0011] Preferably, the acrylate chain extender includes but is not limited to at least one of tripropylene glycol diacrylate, ethylene glycol dimethacrylate (EGDMA) and tripropylene glycol diacrylate (TPGDA).

[0012] Preferably, the chain extender is bis-allyl chain extender allyl diethylene glycol dicarbonate (DOEDB).

[0013] Furthermore, the initiator is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane.

[0014] Furthermore, the auxiliary antioxidant is at least one of a hindered phenol antioxidant and an aromatic amine antioxidant.

[0015] Furthermore, the auxiliary antioxidant includes antioxidant 168; the hindered phenol antioxidant includes at least one of antioxidant 1010 and antioxidant 1135.

[0016] Furthermore, the nucleating agent is polytetrafluoroethylene particles (PTFE), wherein the diameter of the PTFE particles is 0.35 μm-5 μm.

[0017] Furthermore, the plasticizer is at least one of polycaprolactone, polyhydroxy fatty acid, epoxy soybean oil and glycerol.

[0018] Furthermore, the additive is one or more of a reinforcing agent and a flame retardant.

[0019] Furthermore, the reinforcing agent includes one or more of glass fiber, carbon fiber, and ceramic nanoparticles.

[0020] Furthermore, the flame retardant includes one or more of brominated flame retardants, nitrogen-phosphorus flame retardants, and organic flame retardants.

[0021] The method for preparing the above-mentioned fully biodegradable foam plastic comprises the following steps:

[0022] Step (1): weighing PLA, chain extender, initiator, antioxidant, plasticizer, additives, and nucleating agent according to mass fractions;

[0023] Step (2): placing the components weighed in step (1) in a blender and mixing them evenly;

[0024] Step (3): drying the mixture obtained in step (2), adding the mixture into a twin-screw extruder, and extruding and granulating the mixture to obtain PLA material;

[0025] Step (4): drying the PLA material obtained in step (3) and preparing a sample sheet through a flat vulcanizer;

[0026] Step (5): placing the sample sheet prepared in step (4) into an autoclave for foaming, then releasing the pressure and cooling naturally to obtain a PLA foamed material.

[0027] Furthermore, the PLA, initiator, chain extender, antioxidant, plasticizer, additive and nucleating agent in step (1) are dried before use, the drying time is 2h-6h, and the drying temperature is 60°C-90°C.

[0028] Furthermore, in the step (3), the temperature of the screw from the feed section to the die head of the extruder is set to 140°C to 190°C, the screw aspect ratio of the twin-screw extruder is above 64:1, the screw speed is 50rpm to 300rpm, and the hopper feeding rate is 10-15kg / h.

[0029] Furthermore, in the step (4), the PLA material is dried at a temperature of 60°C-80°C and a drying time of 2h-6h; and the temperature of the flat vulcanizing press in the step (4) is 180°C.

[0030] Furthermore, the thickness of the sample slice described in step (4) is 3 mm to 8 mm.

[0031] Furthermore, the foaming described in step (5) includes the following steps: first heating to the melting point of the material or above the melting point (for example, 180°C), then immediately cooling to 115°C-135°C, using a constant pressure injection pump to inject CO2 into the reactor until the pressure in the reactor is 5-15MPa, and saturation for 0.5h-2h; the heating rate is 5°C / min-8°C / min.

[0032] The foaming process of the present invention is to first raise the temperature to the melting point or above the melting point, in order to destroy the existing crystalline region structure in the sample, especially those crystalline regions with complete structures and larger sizes. The presence of these crystalline regions will hinder the diffusion of gas and limit the growth of pores, thereby affecting the expansion ratio, and then quickly cool down to the foaming temperature to obtain a lower crystallinity and a smaller crystal size, because the rapid cooling makes the polylactic acid molecules not have enough time to arrange in order, on the one hand, crystallization can be used as a heterogeneous nucleating agent to promote pore nucleation, and on the other hand, a small crystal size can reduce the obstruction to the diffusion of a physical foaming agent. Relative to conventional methods, the foaming process of the present invention is more conducive to the preparation of high expansion ratio (because the restrictions on physical foaming agents have become smaller) and high cell density foams.

[0033] Furthermore, the pressure relief time in step (5) is 2s.

[0034] The beneficial effects of the present invention are:

[0035] (1) On the one hand, the present invention uses an initiator and a chain extender to prepare PLA with an entangled long-chain branched structure. On the other hand, during the twin-screw extrusion, PTFE as a nucleating agent forms an in-situ fibrous network in the PLA matrix under high shear stress conditions, resulting in physical entanglement. The long-chain branched entanglement and physical entanglement work together to improve the strength and foaming ratio of the PLA matrix.

[0036] (2) The optimized combination of initiator and chain extender reduces the production of gel components and greatly retains the molding and biodegradability of PLA. In addition, under the action of plasticizer, the nucleating agent is evenly dispersed in the PLA resin matrix. The supercritical foaming process with rising and falling temperatures is used to regulate the crystallization properties of the polymer for the modified PLA foaming nucleating agent. The rising and falling temperatures induce PLA crystallization. The interface between the crystalline phase and the amorphous phase can reduce the energy barrier for cell nucleation, promote cell nucleation, effectively increase the cell density, reduce the average diameter of the cell, and improve the compression performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the SEM image of the PLA foam material of Example 4;

[0038] Figure 2 This is the SEM image of the PLA foam material of Example 5;

[0039] Figure 3 This is the SEM image of the PLA foam material of comparative example 2. DETAILED DESCRIPTION

[0040] The above scheme is further described below in conjunction with specific embodiments. The following factual cases are only used for the method used in the present invention, and the specific implementation conditions can be adjusted according to the manufacturer's needs and conditions.

[0041] Unless otherwise specified, the raw materials in the examples of this application were purchased through commercial channels.

[0042] The expansion ratio of the foaming material in the present invention is calculated by the following formula:

[0043]

[0044] Cell size and cell density: Cut the PLA foam material into a flat section with a sharp blade, spray gold on the section, and use a scanning electron microscope (SEM) to observe the cell structure inside the foam material. Use Image J software to measure the cell size and calculate the cell density. The cell density N (unit: cell / cm 3 )=(n / A) 3 / 2 , n is the number of cells on the selected SEM, A is the actual area of ​​the scanned photo (unit: cm 2) .

[0045] Example 1

[0046] A fully biodegradable foam plastic and a preparation method thereof, comprising the following parts by weight:

[0047] 100 parts of PLA, 0.5 parts of chain extender, 0.1 parts of initiator, 0.1 parts of antioxidant, 1 part of nucleating agent, 0.5 parts of plasticizer, and 8 parts of additives; wherein the chain extender is allyl diethylene glycol dicarbonate (DOEDB), the antioxidant is antioxidant 1010, the nucleating agent is PTFE (model F481, purchased from Zhejiang Jiashan Shenjia Technology Co., Ltd.), the plasticizer is polycaprolactone, and the additive is ceramic nanoparticles.

[0048] A method for preparing a supercritical foamed PLA material based on the above includes the following steps:

[0049] Step (1) weighing PLA, chain extender, initiator, antioxidant, plasticizer, additives, and nucleating agent according to mass fractions;

[0050] Step (2) placing the components weighed in step (1) in a blender and mixing them evenly;

[0051] Step (3) drying the mixture obtained in step (2) and then adding it into a twin-screw extruder for extrusion and granulation to obtain PLA material;

[0052] Step (4) drying the PLA material obtained in step (3) and preparing a sample sheet of 1 cm×0.5 cm×0.1 cm by a flat plate vulcanizer at a temperature of 180° C.

[0053] Step (5) Place the sample sheet prepared in step (4) into an autoclave, heat it to 180°C and then immediately cool it to 125°C, use a constant pressure injection pump to inject CO2 into the autoclave until the pressure in the autoclave is 15 MPa, after saturation for 2 hours, release the pressure in the autoclave to normal pressure within 2 seconds, cool it to room temperature, and discharge the material to obtain PLA foam material.

[0054] Example 2

[0055] The difference between Example 2 and Example 1 is that the amount of chain extender added is different, see Table 1.

[0056] Example 3

[0057] The difference between Example 3 and Example 1 is that the addition amount of each component is increased, see Table 1.

[0058] Example 4

[0059] The difference between Example 4 and Example 3 is that the amount of nucleating agent added is different, see Table 1.

[0060] Example 5

[0061] The difference between Example 5 and Example 3 is that the amounts of antioxidant and plasticizer added are different, see Table 1.

[0062] Example 6

[0063] The difference between Example 6 and Example 5 is that the amount of chain extender added is different, see Table 1.

[0064] Example 7

[0065] The difference between Example 7 and Example 6 is that the added chain extender, antioxidant, nucleating agent and plasticizer are different in amount, see Table 1.

[0066] Example 8

[0067] The difference between Example 8 and Example 6 is that the amount of chain extender added is different, see Table 1.

[0068] Comparative Example 1

[0069] The difference between Comparative Example 1 and Example 1 is that no chain extender is used, see Table 1.

[0070] Comparative Example 2

[0071] The difference between Comparative Example 2 and Example 1 is that no nucleating agent is used, see Table 1.

[0072] Comparative Example 3

[0073] The difference between Comparative Example 3 and Example 1 is that trimethylolpropane triacrylate (TMPTA) is used as a chain extender.

[0074] Comparative Example 4

[0075] The difference between Comparative Example 4 and Example 6 is that in step (5), the temperature is directly raised to the foaming temperature of 125°C.

[0076] Table 1 Raw material ratio table of Examples 1-8 and Comparative Examples 1-3

[0077]

[0078] Performance Test:

[0079] The average cell size, cell density and expansion ratio of the PLA foam materials prepared in Examples 1-5 of the present invention are shown in Table 2.

[0080] Table 2 Expansion ratio and cell data statistics of Examples 1-8 and Comparative Examples 1-3

[0081]

[0082]

[0083] From the results in Table 2, it can be seen that, except for Example 6 which contains a small amount of gel component, the other examples using the optimized peroxide and chain extender combination do not contain gel components, thereby retaining the biodegradability of PLA; the introduction of the chain extender forms a long-chain branched structure, which improves the melt strength of the PLA matrix, thereby significantly improving the expansion ratio; the pore size decreases with the increase of the nucleating agent content, and the pore density is significantly improved. In addition, the dense and uniform pore structure improves the compression strength of the foam.

[0084] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.

Claims

1. A fully biodegradable foam plastic, characterized in that: The fully biodegradable foam plastic is prepared from the following raw materials in mass fractions: 100 parts of polylactic acid, 0.1-0.5 parts of initiator, 0.5-3 parts of chain extender, 0.1-0.3 parts of antioxidant, 0.5-2 parts of plasticizer, 8-10 parts of additives and 1-4 parts of nucleating agent.

2. The fully biodegradable foam plastic according to claim 1, characterized in that: The chain extender includes at least one of a diepoxy functional chain extender, a bisallyl chain extender, and a bisacrylate chain extender.

3. The fully biodegradable foam plastic according to claim 2, characterized in that: The diepoxy functionalized chain extender includes at least one of diglycidyl ether and neopentyl glycol diglycidyl ether; And / or, the bisallyl chain extender includes allyl diglycol dicarbonate and bisphenol A bisallyl ether; And / or, the acrylate chain extender includes at least one of tripropylene glycol diacrylate, ethylene glycol dimethacrylate and tripropylene glycol diacrylate.

4. The fully biodegradable foam plastic according to claim 1, characterized in that: The initiator is 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane; and / or, at least one of the auxiliary antioxidant, hindered phenol antioxidant, and aromatic amine antioxidant; and / or, the nucleating agent is polytetrafluoroethylene particles; And / or, the plasticizer is at least one of polycaprolactone, polyhydroxy fatty acid, epoxy soybean oil and glycerol.

5. The fully biodegradable foam plastic according to claim 1, characterized in that: The additive is one or more of a reinforcing agent and a flame retardant; The reinforcing agent includes one or more of glass fiber, carbon fiber, and ceramic nanoparticles; The flame retardant includes one or more of brominated flame retardants, nitrogen-phosphorus flame retardants, and organic flame retardants.

6. A method for preparing a fully biodegradable foam plastic, characterized in that: The method comprises the following steps: Step (1): weigh polylactic acid, initiator, chain extender, antioxidant, plasticizer, additives and nucleating agent according to mass fractions. Step (2): placing the components weighed in step (1) in a blender and mixing them evenly; Step (3): drying the mixture obtained in step (2), adding the mixture into a twin-screw extruder, and extruding and granulating the mixture to obtain PLA material; Step (4): drying the PLA material obtained in step (3) and preparing a sample sheet through a flat vulcanizer; Step (5): placing the sample sheet prepared in step (4) into an autoclave, increasing the temperature and pressure, foaming, and then releasing the pressure to obtain a fully biodegradable foam plastic.

7. The method for preparing a fully biodegradable foam plastic according to claim 6, characterized in that: The polylactic acid, initiator, chain extender, antioxidant, plasticizer, additive and nucleating agent in step (1) are dried before use, the drying time is 2h-6h, and the drying temperature is 60°C-90°C.

8. The method for preparing a fully biodegradable foam plastic according to claim 6, characterized in that: The temperature of the twin-screw extruder in step (3) is set to 140° C. to 190° C., the screw aspect ratio of the twin-screw extruder is above 64:1, the screw speed is 50 rpm to 300 rpm, and the hopper feeding rate is 10-15 kg / h.

9. The method for preparing a fully biodegradable foam plastic according to claim 6, characterized in that: In the step (4), the PLA material drying temperature is 60°C-80°C, and the drying time is 2h-6h; and the temperature of the flat vulcanizing machine in the step (4) is 180°C.

10. The method for preparing fully biodegradable foam plastic according to claim 6, characterized in that: The foaming described in step (5) comprises the following steps: firstly heating to the melting point of the material or above the melting point, then immediately cooling to 115°C-135°C, injecting CO2 into the reactor using a constant pressure injection pump until the pressure in the reactor is 5-15MPa, and saturating for 0.5h-2h; The pressure relief time in step (5) is 2s.